نظام دعم قرار لتقدير الكميات والجدولة الزمنية المثلى لمشروعات الطرق الرئيسية ( HWSDSS ) (Latakia University Journal -Engineering Sciences Series, 2019)
This paper presents HWSDSS the Decision Support System for estimating and scheduling of highway construction projects. HWSDSS integrates the estimating process (calculating the quantity of work for project activities) and the scheduling optimization process. HWSDSS performs the quantity take-off for each activity in each repeated segment based on the ground topography data and the designed cross-sections of the highway. HWSDSS utilize the mixed combinatorial-dynamic programming technique to generate the optimum schedule that corresponding to the planner target (minimum duration, or minimum cost). تقدم هذه الورقة البحثية نظام دعم القرار HWSDSS لتقدير كميات الأعمال والجدولة الزمنية لمشروعات الطرق. النظام بشكل متكامل يقوم بحساب كميات أعمال أنشطة المشروع وإجراءات الجدولة الزمنية المثلى لأنشطة المشروع. يتم حساب كميات الأعمال لكل نشاط في كل قطاع من الطريق بالاعتماد على شكل الأرض الطبيعية والمقطع العرضي التصميمي للطريق. يعتمد النظام على تقنية الجدولة الزمنية " التوافيق-البرمجة الديناميكية المختلطة " لتوليد الجدولة الزمنية المثلى طبقاً لهدف المستخدم ( أقل زمن للمشروع أو أقل كلفة للمشروع).